The Essence Of The Concept Of Freedom In Law - Soliboyev Umidbek (Research Parks Publishing LLC, 2021)
In our article, the role of law in human nature. Principles of different understanding of the concept of freedom in law. Historical manifestations of freedom, reflections on the freedom of existence in practice